1st May: 6th Sunday of Easter - Jamison, Trevor (The expository times, 2016)
The article discusses religious aspects of 1st May of 2016 as the 6th Sunday of Easter. It states views of Saint Paul on visiting Macedonia, and mentions that Paul and his companions traveled to Asia and Europe. It notes significance of Jesus' conversations with Samaritan and Phoenician women, and cites role of Christian missionaries in establishing Christianity.